1992
DOI: 10.1016/0014-5793(92)81493-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor α stimulates sphingomyelinase through the 55 kDa receptor in HL‐60 cells

Abstract: Tumor necrosis ractor a (TNFa) stimulated rapid (seconds) hydrolysis oTsphingomyclin in ML-60 cells, formation of phosphochcline (PCho) and a dmunsc in choline. The response to TNFa was concentration dependent with a muximal et&et at 3-10 nM. The monoclonal antibody (mAb), htr-9, which behaves as an agonist at the 55 kDa subtype of the TNF receptor, also stimulated sphingomyelin hydrolysis in in!act cells. In contrast, the mAb, utr-I, which behaves as an antagonist at the 7.5 kDa receptor subtype, had no et'fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…2B). In accordance with previous observations on fibroblasts (39) or leukemic cells (9,10,46), TNF-␣ also caused a considerable (20%) breakdown of phosphatidylcholine, parallel to the SPM cycle, which also occurred at 14°C (Fig. 2A).…”
Section: Low Temperatures and Hypertonic Media Inhibit Receptormediatsupporting
confidence: 92%
See 1 more Smart Citation
“…2B). In accordance with previous observations on fibroblasts (39) or leukemic cells (9,10,46), TNF-␣ also caused a considerable (20%) breakdown of phosphatidylcholine, parallel to the SPM cycle, which also occurred at 14°C (Fig. 2A).…”
Section: Low Temperatures and Hypertonic Media Inhibit Receptormediatsupporting
confidence: 92%
“…Indeed, down-modulation of the TNF receptors is a result of the internalization of p60 receptor (60). Since the p60 receptor triggers the SPM pathway (10,13,61), it is therefore likely that, under conditions where internalization is blocked, the reversibility of SPM degradation is not due to down-regulation of the TNF receptor.…”
Section: Low Temperatures and Hypertonic Media Inhibit Receptormediatmentioning
confidence: 99%
“…Concurrently with sphingomyelin hydrolysis, TNF-a is known to stimulate PtdCho degradation [28,29,33,43,4.51 (see also Figs 1, 2, 4 and 6). …”
Section: Since Incorporation Of [3h]choline Into Sphingomyelin Is a Tmentioning
confidence: 97%
“…However, other reports indicate no changes in ceramide with TNF-␣ for several hours (24). There is also some controversy as to whether this sphingomyelinase activity is plasma membrane-bound, cytosolic, or lysosomal, or some combination of these (14,23,25,26), but many models proposed rely on this rapid (5-30 min) switching on and off of sphingomyelinase to activate the apoptotic signal. Contrary to the model, several laboratories have reported that ceramide is not necessary for TNF-␣ activation of nuclear factor-B and that the observed effects of ceramide might be nonphysiological (27)(28)(29)(30).…”
mentioning
confidence: 99%